2012
DOI: 10.2967/jnumed.112.103796
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Morphine on Cerebral 5-HT2A Availability in Dogs: a SPECT Study

Abstract: The opioid and serotonergic systems are closely involved in pain processing and mood disorders. The aim of this study was to assess the influence of systemic morphine on cerebral serotonin 2A receptor (5-HT 2A ) binding in dogs using SPECT with the 5-HT 2A radioligand 123 I-5I-R91150. Methods: 5-HT 2A binding was estimated with and without morphine pretreatment in 8 dogs. The 5-HT 2A binding indices in the frontal, parietal, temporal, and occipital cortex and in the subcortical region were obtained by semiquan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Also in recent years, some researchers have studied the influence of morphine on cerebral 5-HT 2A receptor availability in dogs; their results indicated that a single dose of morphine decreased 5-HT 2A receptor binding index in the frontal cortex ( Adriaens et al, 2012 ), but prolonged morphine exposure lowered the 5-HT 2A receptor binding index in frontal, temporal, and parietal cortex as well as subcortical region ( Adriaens et al, 2014 ). These data provide further evidence for the interaction between the opioid and serotonergic system and encourages further research on the possible beneficial effects of opioids in the treatment of mood disorders ( Adriaens et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in recent years, some researchers have studied the influence of morphine on cerebral 5-HT 2A receptor availability in dogs; their results indicated that a single dose of morphine decreased 5-HT 2A receptor binding index in the frontal cortex ( Adriaens et al, 2012 ), but prolonged morphine exposure lowered the 5-HT 2A receptor binding index in frontal, temporal, and parietal cortex as well as subcortical region ( Adriaens et al, 2014 ). These data provide further evidence for the interaction between the opioid and serotonergic system and encourages further research on the possible beneficial effects of opioids in the treatment of mood disorders ( Adriaens et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data provide further evidence for the interaction between the opioid and serotonergic system and encourages further research on the possible beneficial effects of opioids in the treatment of mood disorders ( Adriaens et al, 2014 ). Apparently, the influence of morphine on the availability of 5-HT 2A receptor might be different in the presence of acute noxious stimulation ( Adriaens et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, if the problem of drug abuse is approached as a mental disorder of memory, then pharmacological manipulations that facilitate extinction may hold therapeutic utility for treating drug abuse. Drug exposure alters the expression and function of 5-HT 2A R, for example morphine decreases frontocortical 5-HT 2A R binding affinity in dogs ( Adriaens et al, 2012 ). 5-HT 2 Rs are up-regulated in amygdala, midbrain, pons, and medulla of morphine-tolerant and -dependent rats, but not in morphine-abstinent rats ( Gulati and Bhargava, 1989 ).…”
Section: -Ht 2a R Functions In Cnsmentioning
confidence: 99%
“…This could possibly suggest that morphine exerts its effect at a different level at this time point. On the one hand, changes in the serotonergic neuroreceptor system have been found in a previous study, possibly indicating that the downstream effects of morphine are more important for its effect [34] . On the other hand, a peripheral action (spinal or at the periphery) rather than a supraspinal action could be responsible for the effect of morphine at a later time point.…”
Section: Discussionmentioning
confidence: 64%